The biological bases of social deficits: the roles of social motivation, theory of mind, and selected genotypes (OPRM1, 5-HTTLPR) in autism spectrum disorder - Hamilton, Kate (Department of Psychology, 2021)
Autism Spectrum Disorder (ASD) is a diverse disorder, and the heterogenous range of possible presentations hinders our understanding of its aetiology. Recently there has been a surge of genome wide association studies for ASD, while historically psychological theories were relied on to explain the emergence of ASD. These fields continue to provide insights into ASD, but they tend to operate in parallel – genetic studies often lack comprehensive psychological phenotyping and theoretical backing, and psychological studies tend to lack genetic explanations. I propose that moving forward, genotype-phenotype studies should have a strong foundation in both fields and should focus on genes and theories with realworld implications for ASD diagnostics and/or interventions. This approach can be supported by focusing on established, well supported psychological theories, and selected ASD candidate genes that could be implicated in these theories, and ideally the genetic mechanism implicated should be one that can be targeted by existing medications. I therefore selected two prominent psychological theories, the Social Motivation Theory for ASD (Panksepp, 1979) and the ToM Theory for ASD (Baron-Cohen et al., 1985), and selected an ASD candidate gene that was likely implicated in each of these theories, namely the mu-opioid receptor gene (OPRM1) and the serotonin transporter promoter length polymorphism (5-HTTLPR) respectively. For the first study of this protocol, I assessed the possible relationships between social motivation, OPRM1, and the ASD phenotype. For the second study, I assessed possible relationships between ToM deficits, 5-HTTLPR, and the ASD phenotype. These two studies shared a sample of 153 male children 4-16 years old; 51 boys per group (i.e. non-verbal ASD; verbal ASD; neurotypical). All ASD children completed ADOS2 assessment for ASD phenotyping. For the Social Motivation Study, attachment was used as a proxy to assess level of social motivation in all participants, and 76 of the 102 children with ASD provided DNA for OPRM1 genotyping. Comparisons across all three groups showed that the ASD samples had significantly lower social motivation than the neurotypical sample, with the non-verbal ASD group displaying the most severely reduced level of social motivation. Reduced social motivation was associated with ASD-related deficits in the non-verbal ASD sample but not the verbal ASD sample. Finally, I was unable to statistically assess the role of OPRM1 as hypothesized, due to an unprecedentedly high rate of the OPRM1 G allele, which indicated atypical mu-opioid processes. This clearly implicated OPRM1 in ASD and is the first study to show this so convincingly. Overall, this study's findings led me to suggest that Panksepp's (1979) theory could be updated to include a threshold effect such that more severely reduced social motivation in ASD is associated with little-to-no language acquisition, while those with less severely reduced social motivation are able to develop language and this protects against associations between social motivation and ASD-related deficits in childhood. For the Theory of Mind Study, the verbal ASD sample and neurotypical sample completed a developmental ToM Battery (i.e. University of Cape Town Theory of Mind Battery) and WASI assessment to establish verbal intelligence quotient (VIQ) scores, and 70 of the children with ASD were successfully genotyped for 5-HTTLPR. This study found that verbal male children with ASD tended to be one developmental stage behind age-matched neurotypical peers on ToM tasks. ToM deficits were associated with greater impairment in overall ASD severity and in symptoms from the social communication and interaction domain. For the non-verbal ASD sample, the 5-HTTLPR short allele, which is implicated in atypical serotonergic transmission, was associated with greater impairment overall and in the restricted and repetitive behaviours and interests symptom domain. No associations between 5-HTTLPR and ToM, or with ASD-related symptoms, was found for the verbal ASD group. This again suggested that language acquisition is an important consideration in genotypephenotype studies in male children with ASD.